2012
DOI: 10.1039/c2dt12243j
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(ii) thiocarboxamide complexes: synthesis, characterisation and application to catalytic Suzuki coupling reactions

Abstract: A simple route to synthesise palladium(II) complexes from the reaction of N-substituted pyridine-2-thiocarboxamide ligands and PdCl(2)(PPh(3))(2) has been developed. The new complexes are very soluble in common solvents and have been fully characterised (elemental analysis, FT-IR, (1)H, (31)P, (13)C-NMR), including an X-ray diffraction analysis. The molecular structures of all the complexes were determined and reveal the presence of square planar geometry around Pd with little distortion. The complexes were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Complexes 4 and 5 displayed one singlet in their 31 P NMR spectra between 37.85 ppm and 30.63 ppm respectively (Figures S1). These values fall within typical 31 P NMR signals between 30.70-35.70 ppm for related mono-coordinated PPh 3 compounds and agrees with the proposed structures in Scheme 2[30][31][32][33][34][35][36][37]. Mass spectrometry was also used to establish the formation and identity of these complexes.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Complexes 4 and 5 displayed one singlet in their 31 P NMR spectra between 37.85 ppm and 30.63 ppm respectively (Figures S1). These values fall within typical 31 P NMR signals between 30.70-35.70 ppm for related mono-coordinated PPh 3 compounds and agrees with the proposed structures in Scheme 2[30][31][32][33][34][35][36][37]. Mass spectrometry was also used to establish the formation and identity of these complexes.…”
mentioning
confidence: 55%
“…Crystal data collection and structural refinement parameters are given in [40][41][42]. Significant distortions from the ideal square planar geometry were evident in bond angles for N(2)-Pd(01)-P(003) of 94.19(5)° and C(1)-Pd(01)-P(004)of 87.54(7)° presumably due to steric demands of the two bulkier PPh 3 groups.…”
Section: Methodsmentioning
confidence: 99%
“…For example, N-alkylbenzoylthiourea ligands can give stable complexes with various transition metals including Cu and Ni in which they act as bidentate O,S donor ligands [12,13]. In addition, the presence of hard nitrogen and soft sulfur donor atoms provides a multitude of bonding possibilities; moreover, an additional donor group such as pyridyl residue in the ligand can change the coordination behavior of benzoyl thiourea to act as a N,S-bidentate ligands [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…The application of complexes containing sulfur or nitrogen as phosphine free catalytic systems were developed recently to eliminate or reduce costs, operational hazards and environmental pollution [22,23]. For example, Sindhuja et al reported the synthesis and application of palladium catalysts containing modified sulfur ligands which can accelerate the coupling reactions of aryl bromides with phenylboronic acid [24]. It was found that the release of Pd(0) species in such cross-coupling reactions depends on the nature of the ligands around the palladium centre [25].…”
mentioning
confidence: 99%